Palladium-catalyzed ring-opening reactions of cyclopropanated 7-oxabenzonorbornadiene with alcohols - Tait, Katrina; Alrifai, Oday; Boutin, Rebecca; Haner, Jamie; Tam, William (Beilstein Journal of Organic Chemistry, 2016)
Palladium-catalyzed ring-opening reactions of cyclopropanated 7-oxabenzonorbornadiene derivatives using alcohol nucleophiles were investigated. The optimal conditions were found to be 10 mol % PdCl2(CH3CN)2 in methanol, offering yields up to 92%. The reaction was successful using primary, secondary and tertiary alcohol nucleophiles and was compatible with a variety of substituents on cyclopropanated oxabenzonorbornadiene. With unsymmetrical C1-substituted cyclopropanated 7-oxabenzonorbornadienes, the regioselectivity of the reaction was excellent, forming only one regioisomer in all cases.
Keywords: alcohol nucleophiles; C1 substitution; cyclopropanated oxabenzonorbornadiene; palladium catalysis; ring-opening reactions